2015
DOI: 10.1177/0021998315613129
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of mechanical properties of randomly oriented strand thermoplastic composites

Abstract: There is an emerging interest in the aerospace industry to manufacture components with intricate geometries using discontinuous fibre carbon/polyether–ether–ketone moulding systems (obtained by cutting unidirectional tape into strands). This type of material system is termed randomly oriented strand composites and is appealing for structural applications as it bridges the gap between the lack of formability of continuous fibre composites and the lack of performance of short fibre composites. The objective of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

9
128
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 92 publications
(138 citation statements)
references
References 11 publications
9
128
0
1
Order By: Relevance
“…In addition, practical advantages of ultrathin CTTs (UTÀCTTs) were described, 22 by using small specimens to obtain elastic parameters for computer-aided engineering (CAE) applications. Selezneva et al 18 theoretically predicted randomly oriented strands (ROS) tensile strength and tensile modulus values; however, a perfect agreement with the experimental results was not achieved. Although some studies have suggested various prediction models for estimating the tensile modulus and strength of the CTTs, their dependence on the tape length was not successfully reproduced (especially for the material tensile strength).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, practical advantages of ultrathin CTTs (UTÀCTTs) were described, 22 by using small specimens to obtain elastic parameters for computer-aided engineering (CAE) applications. Selezneva et al 18 theoretically predicted randomly oriented strands (ROS) tensile strength and tensile modulus values; however, a perfect agreement with the experimental results was not achieved. Although some studies have suggested various prediction models for estimating the tensile modulus and strength of the CTTs, their dependence on the tape length was not successfully reproduced (especially for the material tensile strength).…”
Section: Introductionmentioning
confidence: 99%
“…Several researchers have attempted to evaluate the mechanical properties of the chopped tape-containing composite materials theoretically. 16,18,21,22 Thus, Feraboli et al 16 conducted tensile testing of a chopped CF tape-reinforced epoxy material and predicted its tensile modulus value by using a finite element method, which was based on the classical lamination theory and involved the generation of random numbers. Sato et al 21 and Zhang 22 investigated CTT stochastic properties by utilizing both Monte Carlo simulations and the classical lamination theory and proposed a useful model for predicting tensile modulus values based on the elastic properties of unidirectional materials.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the discontinuous nature of the tows, these materials can be compression-moulded, which significantly improves their manufacturability. In addition, the tow-based architecture of TBDCs allows for a high fibre-content, leading to high modulus and toughness [1][2][3][4][5][6]. This combination of manu-facturability and good mechanical properties makes TBDCs appealing for high-volume production of structural components.…”
Section: Introductionmentioning
confidence: 99%
“…It is agreed that both the modulus [1,[4][5][6]14] and the tensile strength [2,4,6] of TBDCs increase with increasing the tow length or decreasing the tow count (number of fibres in the cross-section of a tow) [5,15]; this effect is much more pronounced on the strength than on the modulus [4,6], and for sufficiently slender tows the modulus of TBDCs actually converges to that of equivalent laminates [6,14].…”
Section: Introductionmentioning
confidence: 99%